Pendampingan Implementasi Materi Berpikir Komputasional di Mata Pelajaran Informatika Pada Kurikulum Merdeka Tingkat SMP di Wilayah Kabupaten Bandung - Ema Rachmawati; Fazmah Arif Yulianto; Lidya Ningsih (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
In the era of globalization and digitalization, mastery of Computational Thinking (CT) has become crucial in computer science education, especially at the junior high school level. This mentoring program is designed to bridge the gap between the evolving curriculum demands and teachers' readiness to implement them, with a specific focus on CT content in the Informatics subject for junior high schools. The activities involve teaching technical aspects of informatics and providing a deep understanding of computational thinking as an essential tool for developing students' analytical, creative, and problem-solving abilities. By enhancing the capabilities of junior high school informatics teachers, this program aims to improve the quality of education and equip teachers with relevant skills to teach CT material to students, thereby contributing to community empowerment through the overall enhancement of digital literacy.